2022
DOI: 10.2147/jir.s378212
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Metabolic-Related Signature CYP19A1 is a Potential Biomarker for Prognosis and Immune Cell Infiltration in Gastric Cancer

Abstract: Background: Altered lipid metabolism is associated with gastric cancer (GC) progression. Comprehensive analysis to identify critical lipid metabolic drivers for predicting overall survival (OS) is not fully elucidated in GC. Our study aim to explore a novel lipid metabolism-related prognostic marker for GC. Methods: Transcriptional status and clinical features were obtained from the TCGA-STAD database. The differentially expressed lipid metabolic genes and the risk prognostic model were developed by using bioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…MAGEA11 was previously found to be highly expressed in breast cancer, bladder cancer, and laryngeal squamous cell carcinoma 26 28 ; the positive expression of this gene was associated with the progression of malignant tumors, thus leading to poor survival 29 , 30 . CYP19A1 , a member of the cytochrome P450 family, was previously found to be highly expressed in GC and associated with an adverse prognosis; the silencing of its expression could be useful for GC treatment 31 , 32 . A previous study showed that SHOX2 methylation represent a potential biomarker for some cancers 33 37 .…”
Section: Discussionmentioning
confidence: 99%
“…MAGEA11 was previously found to be highly expressed in breast cancer, bladder cancer, and laryngeal squamous cell carcinoma 26 28 ; the positive expression of this gene was associated with the progression of malignant tumors, thus leading to poor survival 29 , 30 . CYP19A1 , a member of the cytochrome P450 family, was previously found to be highly expressed in GC and associated with an adverse prognosis; the silencing of its expression could be useful for GC treatment 31 , 32 . A previous study showed that SHOX2 methylation represent a potential biomarker for some cancers 33 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer, BCHE expression is down-regulated early on and up-regulated in the late stage ( 75 ). Cytochrome P450 family 19 subfamily A member 1 (CYP19A1) can catalyze the conversion of androgen/testosterone to estradiol/estrone, the main enzyme involved in estrogen production ( 76 ). Breast cancer, endometrial cancer, and Alzheimer’s disease are intimately associated with CYP19A1 ( 77 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…CYP19A1 catalyzes the synthesis of steroids, which are involved in the development of gastric cancer [29]. Based on immunohistochemistry fndings, CYP19A1 has been reported to be upregulated in gastric cancer tissues, and it has been suggested as an independent biomarker for gastric cancer [30]. Phytomedicines that induce downregulated CYP19A1, such as ursolic acid and taxifolin, reduce the malignancy and progression of gastric cancer [31,32].…”
Section: Discussionmentioning
confidence: 99%